Effects of maternal anaemia on neonatal outcome a study done in the specialized urban hospital set up in Bangladesh (Bangladesh Journal of Medical Science, 2011)
Context: Anaemia is a common pregnancy related disorder in Bangladesh that causes various maternal and fetal problems. A prospective study was designed to see the associated maternal factors and fetal outcome in different categories of anaemia and to compare with that of normal pregnancy. Methods: The study was carried out on 60 Bangladeshi women within 35-40 weeks of gestation. Among them, 20 with normal uncomplicated pregnancies were considered as control group or group A, another 27 having pregnancies with mild anaemia were considered as group B, and 13 having pregnancies with moderate anaemia were considered as group C. Severe anaemic mothers were considered as group D, but not found during the period of collection of data for this study. The mothers were selected as who were suffering from antenatal anaemia i.e. having heamoglobin level